Topical issues of personnel training in the field of unmanned aircraft systems - I. V. Blagodaryashchev; M. A. Kiselev; R. S. Naumov; V. S. Shapkin (Научный вестник МГТУ ГА)
The legal regulation, and hence, the training system in the field of unmanned aircraft systems (UAS) in the Russian Federation, the European Union and the United States is based on the unmanned aerial vehicles (UAV) rating with respect to UAS maximum take-off weight (MTOW) and their purpose (method of use). In this regard, small-unmanned aircraft (sUAS) are identified – in our country up to 30 kg, in the EU and the USA up to 55 lbs (25 kg) and UAV with larger weight. In the USA and Europe, the training of remote pilots for sUAS is differentiated based on the degree of risk that UAV can represent for public safety. Thus, the training of remote pilots to use UAVs with MTOW less than 25 kg (55 lbs) in a sparsely populated area during daylight hours under the conditions of visual range is conducted in the online format, the result of which is taking tests. In the United States and Europe, the UAV application with MTOW more than 25 kg (55 lbs) or performing UAV operations, presenting a potential risk for public safety, requires more comprehensive and long-term training of remote pilots. In the Russian Federation, UAS personnel training is conducted in educational organizations according to different programs, which vary significantly depending on a specific type of aviation UAVs refers to: State, Civil or Experimental. UAS personnel training programs for various aviation types are not harmonized, which leads to the failure to credit previously received education in training to perform activities in another aviation type. The article describes the analysis results of the international and national experience, perspectives for the development of the UAS personnel training system, as well as formulates the proposals concerning further development of the national system for UAS specialists training.